2008
DOI: 10.1093/jat/32.8.621
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Drug Concentrations Taken From Clamped and Unclamped Femoral Vessels

Abstract: Postmortem drug concentrations may vary depending on sampling site, volume of blood collected, and method of sampling, making it important to analyze specimens from different sites in the body to detect postmortem redistribution and avoid erroneous conclusions on cause and manner of death. Using a blind stick method to draw large amounts of blood from the femoral vessel may increase the likelihood of contamination with blood from more central sites. It has been suggested that clamping the femoral vessel before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 0 publications
1
13
0
2
Order By: Relevance
“…Evaluation of different sampling techniques has yielded similar results. 27 A systematic study involving duplicate sampling from the femoral veins showed a considerable random sampling variation yielding a preanalytical uncertainty component superseding the analytical variation considerably. 28 …”
Section: Postmortem Sampling Conditionsmentioning
confidence: 99%
“…Evaluation of different sampling techniques has yielded similar results. 27 A systematic study involving duplicate sampling from the femoral veins showed a considerable random sampling variation yielding a preanalytical uncertainty component superseding the analytical variation considerably. 28 …”
Section: Postmortem Sampling Conditionsmentioning
confidence: 99%
“…La influencia de las condiciones preanalíticas sobre la incertidumbre de la medida de concentración puede ser importante e incluso mayor que la incertidumbre asociada al método analítico 16 . Por ejemplo, se ha demostrado que la incertidumbre asociada a la concentración de metadona en sangre femoral se incrementa 5 veces cuando se tienen en cuenta los factores preanalíticos 17 .…”
Section: Condiciones Preanalíticas: Características De La Muestra Anaunclassified
“…Although some ME/Cs ligate the femoral vein and draw distal to the ligation under direct visualization, at least one study shows that samples drawn by blind stick access to the femoral vein yield closely comparable concentrations [18]. If femoral vein blood is not available, then blood from the subclavian vein, the right atrium of the heart, or any other intact blood vessel is the next choice, listed in decreasing order of desirability [8].…”
Section: When Is It Appropriate or Necessary To Perform Toxicology Tementioning
confidence: 99%